The effects of applying communicative language teaching method on 10th EGB students at unidad educativa Monseñor Roberto Maria del Pozo high school during the school year 2017-2018 to overcome speaking anxiety issues - Cusme Campos, Andrea Stefanía (2018)
One important factor in the acquisition of a new language is to know the difference between traditional teaching methods and the current ones. Every person is a unique world and teachers need to be aware of the newest techniques to adapt in the classrooms. Facilitators of English should focus on meaning and communication in order to develop the communicative competence in the students through meaningful interaction. Focusing on the Communicative Approach is about exchanging information that is integral and relevant to events and experiences in students’ daily lives. It is necessary to be attentive that English has been taught to people and not machines, so memorizing should not be the best option in order to acquire a different language. Students can be prepared and relaxed when facing an opportunity to produce English, forgetting about Speaking Anxiety……….